Nigerian democratic behaviour and protest reportage in 2015 general elections - Ani, Kelechi Johnmary (Penerbit Universiti Kebangsaan Malaysia, 2024)
Over the ages, the media have been charged with the statutory role of enhancing individual and societal well-being through unfettered sharing of information, values and opinions to engender informed decisions especially on political matters. Through communication, the mass media strengthens the capacity of individuals and groups in the society towards actively contributing to democratic growth, electoral behaviour and development. The question: how far have the media succeeded in discharging this social responsibility in Nigeria? It remains a burning national issue. This study presents the media role in expanding the democratic horizon in the country by focusing on the 2015 general elections and the reportage of protests that followed. The article went further to identify the diverse challenges facing the media, which include misinformation, stereotype and insecurity of journalists and offers plausible recommendations for enhancing the place of the media in democratic culture and governance in Nigeria. The study used mixed method to gather materials from the field on electoral protests. Histogram were used to present a clear analysis of findings, which were supported by secondary research. It found that there were discrepancies in the election reportage and also that the protests, which manifested during the election affected nation building activities and electoral behaviour in many parts of Nigeria. It consequently recommends peace journalism and improved media training for Nigerian journalists.